Enforcement of the Advocate's Code of Ethics among Fellow Law Enforcers (Catur Wangsa) - Yeti Kurniati; Jhon Asron Purba; Rusdi Rusdi; Roni Eka Putra (Journal of Social Research, 2026)
This research examines the enforcement of the Advocate's Code of Ethics among fellow law enforcers in Indonesia, particularly in relation to the interactions between advocates, police officers, prosecutors, and judges within the criminal justice system. The study aims to analyze how violations of the Advocate's Code of Ethics affect the judicial process and to assess the effectiveness of existing enforcement mechanisms. A qualitative normative legal research approach was employed, focusing on secondary legal materials such as legislation, court decisions, and professional ethical guidelines. Data were collected through library research, drawing on legal documents and codes of ethics to examine the relationship between advocates and other law enforcement professionals within the Catur Wangsa framework. The findings indicate that breaches of professional ethics such as contemptuous conduct toward law enforcement officers or undue judicial influence adversely affect the integrity of the legal system. Such violations are subject to sanctions ranging from formal warnings to temporary suspension and, in severe cases, permanent dismissal from the professional organization. The study underscores the need for strengthened enforcement of the Advocate's Code of Ethics to uphold the fairness and transparency of the judicial process. This research offers significant insights into how the legal profession can cultivate greater accountability and mutual respect among law enforcement institutions, thereby contributing to a more equitable legal system in Indonesia.